2000
DOI: 10.1016/s0735-1097(99)00558-6
|View full text |Cite
|
Sign up to set email alerts
|

Contrast echocardiography clarifies uninterpretable wall motion in intensive care unit patients

Abstract: CE should be used in all ICU patients with suboptimal transthoracic echocardiograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 15 publications
3
76
1
2
Order By: Relevance
“…Secondary generation transpulmonary contrast agents increase backscatter in an ultrasound field and opacify the left ventricular cavity. Some studies demonstrated an improvement of endocardial border delineation at rest and during stress testing after the administration of a transpulmonary contrast agent (11)(12)(13)(14). In the present study, at-rest echochardiography graded 536 of 992 (54%) myocardial segments as a score of 2 and peak DSE graded only 434 of 992 (44%) segments as a score of 2 before the intravenous bolus of SonoVue or Optison because of an invisible or barely visible left ventricular endocardial border.…”
Section: Discussionsupporting
confidence: 45%
“…Secondary generation transpulmonary contrast agents increase backscatter in an ultrasound field and opacify the left ventricular cavity. Some studies demonstrated an improvement of endocardial border delineation at rest and during stress testing after the administration of a transpulmonary contrast agent (11)(12)(13)(14). In the present study, at-rest echochardiography graded 536 of 992 (54%) myocardial segments as a score of 2 and peak DSE graded only 434 of 992 (44%) segments as a score of 2 before the intravenous bolus of SonoVue or Optison because of an invisible or barely visible left ventricular endocardial border.…”
Section: Discussionsupporting
confidence: 45%
“…1,3 The introduction of transpulmonary contrast agents has further reduced the number of suboptimal cases 1,4 and are useful for endocardial border delineation (EBD) at rest and during stress echocardiography. 1,[4][5][6][7][8] From September 1999, an-air-filled contrast agent, Levovist, became commercially available in Japan for LV border delineation and myocardial perfusion. The rapid advancement in ultrasound technology and improved understanding of microbubble properties, together with a different dosing regimen in Japan (2.5 g vial up to 300 mg/ml) vs Europe (4.0 g vial up to 400 mg/ml) could account for the differing results from previous studies.…”
mentioning
confidence: 99%
“…Critically ill patients are the ones targeted with the new contraindications, as well as the population in whom contrast is most helpful for improving test accuracy, which guides patient management. 2 Likewise, the inconvenience of having to monitor healthy outpatients for 30 minutes after the infusion could so severely affect the dynamics of an echocardiography laboratory that contrast would not be used in technically difficult outpatients. Again, this could lead to further unnecessary testing.…”
Section: The Concern About Safety and Fda Box Warningmentioning
confidence: 99%
“…Multiple studies have reported that these agents improve the accuracy in determining LV volumes, ejection fraction (EF), and regional wall motion abnormalities (Table 2). 2,[7][8][9] In a recent meta-analysis, the correlation coefficient compared with a variety of established standard methods improves with contrast from 0.84 to 0.93. 5 Reproducibility of echocardiography is significantly better when contrast is added to contemporary harmonic imaging.…”
Section: The Need For Contrast Echocardiography In Clinical Practicementioning
confidence: 99%